2021
DOI: 10.1038/s41598-021-94754-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative multiparametric MRI as a non-invasive stratification tool in children and adolescents with autoimmune liver disease

Abstract: Autoimmune hepatitis (AIH) and autoimmune sclerosing cholangitis (ASC) are two very closely related autoimmune liver diseases with overlapping clinical features and similar management strategies. The purpose of this study was to assess the utility of quantitative imaging markers to distinguish ASC from AIH in paediatrics. 66 participants (N = 52 AIH, N = 14 ASC) aged 14.4 ± 3.3 years scheduled to undergo routine biopsy and baseline serum liver biochemistry testing were invited to undergo MRI (non-contrast abdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…12 LiverMultiScan has also shown utility within the AIH context to significantly impact clinical decision-making and physician intended patient management plans, 23 as well as showing utility in longterm management of paediatric patients. 11 The National Institute for Health Research (NIHR) has shown that by conducting early economic evaluation of diagnostic techniques, modelling can reduce commercial risk by providing evidence on cost-effectiveness. 24 Typically, a hypothetical early economic model is developed to compare the indicative cost consequences of using a different method versus standard testing for a particular patient group within a healthcare setting and highlight the clinical need for the proposed technology.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 3 more Smart Citations
“…12 LiverMultiScan has also shown utility within the AIH context to significantly impact clinical decision-making and physician intended patient management plans, 23 as well as showing utility in longterm management of paediatric patients. 11 The National Institute for Health Research (NIHR) has shown that by conducting early economic evaluation of diagnostic techniques, modelling can reduce commercial risk by providing evidence on cost-effectiveness. 24 Typically, a hypothetical early economic model is developed to compare the indicative cost consequences of using a different method versus standard testing for a particular patient group within a healthcare setting and highlight the clinical need for the proposed technology.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“… 12 LiverMultiScan has also shown utility within the AIH context to significantly impact clinical decision-making and physician intended patient management plans, 23 as well as showing utility in long-term management of paediatric patients. 11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 14 Very recently, 2 studies conducted in 65 and 76 adult persons with PSC found that MRCP+ metrics were significantly associated with biochemical prognostic scores and liver stiffness measurement (LSM) and suggested a role for refining risk stratification. 15 , 16 MRCP+ metrics have also shown utility in characterising disease, stratification, and monitoring in paediatric patients 17 , 18 ; however, at present, there are no studies that have investigated the correlation between MRCP+ and clinical outcomes in PSC. Therefore, here, we aimed to assess the role of MRCP+ for detecting biliary changes in a large retrospective cohort of people with PSC and to explore their association with disease severity and clinical outcome.…”
Section: Introductionmentioning
confidence: 99%